Safety Evaluation of Chicken Satay In Yogyakarta Indonesia Based on Benzo[A]Pyrene Content - Irnanda, Khairunissa; Meiftasari, Argandita; Nagadi, Standie; Lukitaningsih, Endang (Indonesian Journal of Cancer Chemoprevention, 2012)
Chicken  satay  is  one  of  Indonesian  food  which  is  very  popular  and  processed  by direct  flame  over  the  meat.  But,  almost  every  types  of  food  which  are  prepared  by  direct flame  will  produce  chemical  compounds  that  contributes  to  the  incidence  of  cancer. Polycyclic aromatic hydrocarbons (PAH) is a group of compound which can cause cancer and is  resulted  from  the  incomplete  combustion  of  fossil  fuels  or  pyrolysis  of  organic  material containing  carbon  and  hydrogen  atoms.  One  PAH  compound  having  mutagenic  and  highly carcinogenic  effect  is  benzo[a]pyrene  which  is  the  highest  content  found  in  foods  that  are burned directly on the flame. This study aims to establish levels of benzo[a]pyrene contained in  chicken  satay  in  Yogyakarta,  Indonesia  and  to  evaluate  how  it  meets  with  the maximumbenzo[a]pyrene  limit  in  the  burned  food  based  on  National  Agency  of  Drug  and Food  Control  which  is  equal  to  5  ppb  (5  mg/kg).  Analysis  were  performed  by  Gas Chromatography  method  using  helium  as  carrier  gas  and  CPCB-Sil8  as  stationary  phase. After  the  sample  was  prepared  and  analysed  by  GC,  it  is  known  that  the  amount  of benzo[a]pyrene in chicken satay found in Yogyakarta are ranging from 2.5 to 393.32 ppb. The result are quite high and far  above the safety limit determined by  National Agency of Drug and Food Control.Therefore, the result of the research needs to be socialized to the public so that people can be more aware about the danger of food they consume.Keywords: chicken  satay,  benzo[a]pyrene  (BaP),  policyclic  aromatic  hidrocarbon  (PAH), carsinogen, Yogyakarta